2002
DOI: 10.3363/prb1992.14.0_129
|View full text |Cite
|
Sign up to set email alerts
|

OLIGOMERIZATION OF ETHENE OVER SEVERAL CATALYST BEDS CONSISTING OF BOTH Ni/SiO<SUB>2</SUB>&middot;Al<SUB>2</SUB>O<SUB>3</SUB> AND BPO<SUB>4</SUB>

Abstract: The oligomerization of ethene was investigated over several catalysts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…265 Initial catalysts contained 2.7 wt% Ni and 13 wt% Al and were activated in air at 540°C. The use of solid Lewis acids was mentioned once by Sakaguchi et al 266 allows almost full selectivity to hexenes. In a similar way for oligomerization of butenes, selectivity for dimers of 95 wt% can be obtained at a partial butene conversion of 30 wt% at 100°C, even after catalyst regeneration under a nitrogen flow.…”
Section: Amorphous Aluminosilicates 531mentioning
confidence: 99%
See 2 more Smart Citations
“…265 Initial catalysts contained 2.7 wt% Ni and 13 wt% Al and were activated in air at 540°C. The use of solid Lewis acids was mentioned once by Sakaguchi et al 266 allows almost full selectivity to hexenes. In a similar way for oligomerization of butenes, selectivity for dimers of 95 wt% can be obtained at a partial butene conversion of 30 wt% at 100°C, even after catalyst regeneration under a nitrogen flow.…”
Section: Amorphous Aluminosilicates 531mentioning
confidence: 99%
“…265 Initial catalysts contained 2.7 wt % Ni and 13 wt % Al and were activated in air at 540 °C. The use of solid Lewis acids was mentioned once by Sakaguchi et al 266 For ethylene oligomerization, Shell also described commercial amorphous aluminosilicates containing aluminum and nickel in similar compositions to the Phillips patents, that is to say between 10 and 30 wt % Al and between 1 and 10 wt % Ni on a metal base. Promotion by 0.3 wt % sulfur, by means of dimethyldisulfide (DMDS), slightly lowers the activity but shifts the selectivity toward 1-hexene, linear octenes and a minority of longer, even numbered olefins.…”
Section: Silicas-ni/siomentioning
confidence: 99%
See 1 more Smart Citation
“…These catalysts can also be successfully used for the oligomerization of propene and butene. [79] Sakaguchi et al [80] have reported that combined use of Ni-silica alumina and BPO 4 is more effective promoting the oligomerization of ethylene than Ni silica alumina alone. An increased C 6 fraction and an equilibrium mixture of n-butene was formed as C 4 products using the catalyst combination, whereas on Ni-silica alumina alone 1-butene was mainly obtained.…”
Section: Nickel Supported Aluminosilicates As Catalystsmentioning
confidence: 99%